The Da Vinci code : a novel - Brown, Dan 1964- (Daniel James) (New York : Doubleday, 2003)
When the curator is found dead in the Louvre, Harvard symbologist Robert Langdon is called in to decipher a series of clues that will lead to the murderer and a conspiracy that has spanned nations and centuries
This is a book discussion kit containing 14 copies in a plastic container. Discussion questions are enclosed. Please stop at the Manitowoc Public Library Youth Reference Desk or call 683-4863, option 6 to reserve the kit in advance
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Appreciation -- Fiction; Leonardo, -- da Vinci, -- 1452-1519; Jesucristo -- Curiosidades y enigmas -- Novela; Art museum curators -- Crimes against -- Fiction; Secret societies -- Fiction; Cryptographers -- Fiction; Grail -- Fiction; Novela estadounidense; Símbolos -- Novela; Sociedades secretas -- Novela; Paris (France) -- Fiction; Mystery fiction